Implementation and evaluation of the WHO maternity care model: a convergent parallel mixed-methods study protocol - Abdolalipour, Somayeh; Abbasalizadeh, Shamsi; Mohammad-Alizadeh-Charandabi, Sakineh; Abbasalizadeh, Fatemeh; Jahanfar, Shayesteh; Mirghafourvand, Mojgan (Frontiers in Global Women's Health, 2024)
Background According to the World Health Organization (WHO), intrapartum care is considered a platform for providing respectful, personalized, and women-centered services to women. This study aims to investigate the intrapartum care model proposed by WHO. Methods This convergent parallel mixed-methods study will be carried out in qualitative and quantitative phases. In the quantitative phase (a quasi-experimental study), 108 pregnant women admitted to the maternity ward will be randomized to intervention (receiving intrapartum care based on the WHO model) and control group (receiving routine hospital care) before the beginning of the active stage of labor (cervix dilatation equal to 5 cm) and Wijma's delivery fear scale (DFS) will be completed for them and again at 7–8 cm dilatation. The participants of both groups will be followed up for 6 weeks after labor and then they will be invited to a relatively quiet place to complete the Childbirth Experience Questionnaire (CEQ 2.0), the Edinburgh Postpartum Depression Scale (EPDS), the Post-Traumatic Stress Disorder (PTSD) Symptom Scale (PSS-I), the Pregnancy and Childbirth Questionnaire (PCQ), exclusive breastfeeding and a checklist on willingness to give birth to another child. The qualitative phase will employ content analysis to explain mothers' views about the effects of this model especially subjective components of this model on their labor process after 4–6 weeks. The two phase's results will be discussed in combination. Discussion The implementation of such care models is expected to prevent mental disorders caused by negative experiences of childbirth, and also, prevent uncontrolled increases in cesarean sections. Clinical Trial Registration https://fa.irct.ir/user/trial/68313/view, identifier (IRCT20120718010324N69).